Formulating Basic Spatial Design Standards For Vertical Rental Housing For Industrial Workers In Karawang Regency - Endah Tisnawati; Rizky Gilang Fadillah; Hestin Mulyandari (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
Karawang Regency is one of Indonesia’s major industrial growth areas, attracting a large number of workers who require decent, affordable, and accessible housing near workplaces. However, the provision of simple vertical rental housing for industrial workers cannot be formulated only through minimum technical building standards, because workers have diverse residential status, household composition, economic capacity, work patterns, and daily mobility. This study aims to formulate the spatial and facility requirements of simple rental vertical rental housing for industrial workers in Karawang based on user characteristics and residential behavior. The study applies a descriptive-qualitative approach based on architectural design inquiry. Data were collected through literature review, site observation, precedent studies, regulatory review, and analysis of user activities. The analysis traces the relationship between worker characteristics, housing needs, daily activities, spatial requirements, space types, spatial character, and basic design principles. The findings show that industrial workers should be understood as heterogeneous users, including single workers, partnered workers, and small-family workers, each with different privacy needs, activity patterns, and facility demands. The required spaces include private dwelling units, service areas, transitional spaces, communal areas, and supporting facilities such as motorcycle parking, laundry areas, drying spaces, small shops or cooperatives, prayer rooms, management offices, security posts, open spaces, and health facilities. The study concludes that basic design standards for workers’ vertical rental housing should emphasize affordability, spatial efficiency, privacy, resting comfort, daylighting, natural ventilation, safety, ease of maintenance, workplace accessibility, and social spaces that do not disturb private areas.